The most likely club - Friedland, Elyssa (Berkley, 2022)
"At their milestone high school reunion, a group of friends makes a pact to finally achieve their high school superlatives one way or another in this lively new novel from the acclaimed author of Last Summer at the Golden Hotel. In 1997, grunge is king, Titanic is a blockbuster (and Blockbuster still exists), and Thursday nights are for Friends. In Bellport, Connecticut, four best friends and high school seniors are ready to light the world on fire. Melissa Levin, Priya Chowdhury, Tara Taylor, and Suki Hammer are going places. Their yearbook superlatives confirm it: Most Likely to Win the White House, Cure Cancer, Open a Michelin-Starred Restaurant, and Join the Forbes 400. Fast-forward twenty-five years and nothing has gone according to plan as the women regroup at their dreaded high school reunion. When a forgotten classmate emerges at the reunion with a surprising announcement, the friends dig out the yearbook and rethink their younger selves. Is it too late to make their dreams come true? Fueled by nostalgia and one too many drinks, they form a pact to push through their middle-aged angst to bring their teenage aspirations to fruition, dubbing themselves the "Most Likely Girls." Through the ensuing highs and lows, they are reminded of the enduring bonds of friendship and the ways our childhood dreams both sustain and surprise us-and why it's deeply uncool to peak in high school"--